Calcium currents in GH3 cultured pituitary cells under whole-cell voltage-clamp: inhibition by voltage-dependent potassium currents. - Barros, F (1985)
To isolate inward Ca2+ currents in GH3 rat pituitary cells, an inward Na+ current as well as two outward K+ currents, a transient voltage-dependent current (IKV) and a slowly rising Ca2+-activated current (IKCa), must be suppressed. Blockage of these outward currents, usually achieved by replacement of intracellular K+ with Cs+, reveals sustained inward currents. Selective blockage of either K+ current can be accomplished in the presence of intracellular K+ by use of quaternary ammonium ions. When IKCa and Na+ currents are blocked, the net current elicited by stepping the membrane potential (Vm) from -60 to 0 mV is inward first, becomes outward and peaks in 10-30 msec, and finally becomes inward again. Under this condition, in which both IKV and Ca2+ currents should be present throughout the duration of the voltage step, the Ca2+ current was not detected at the time of peak outward current. That is, plots of peak outward current vs. Vm are monotonic and are not modified by nisoldipine or low external Ca2+ as would be expected if Ca2+ currents were present. However, similar plots at times other than at peak current are not monotonic and are altered by nisoldipine or low Ca2+ (i.e., inward currents decrease and plots become monotonic). When K+ channels are first inactivated by holding Vm at -30 mV, a sustained Ca2+ current is always observed upon stepping Vm to 0 mV. Furthermore, substitution of Ba2+ for Ca2+ causes blockage of IKV and inhibition of this current results in inward Ba2+ currents with square wave kinetics. These data indicate that the Ca2+ current is completely inhibited at peak outward IKV and that Ca2+ conductance is progressively disinhibited as the transient K+ current declines due to channel inactivation. This suggests that in GH3 cells Ca2+ channels are regulated by IKV.